Management of Perforated Colon Cancers. Issue 3 (July 2014) - Ozogul, Bunyami; Kisaoglu, Abdullah; Ozturk, Gurkan; Atamanalp, Sabri Selcuk; Yıldırgan, Mehmet İlhan and Aydinli, Bulent
No abstract available